Disabled upon arrival : eugenics, immigration, and the construction of race and disability - Dolmage, Jay (The Ohio State University Press, 2018)
"In North America, immigration has never been about immigration. That was true in the early twentieth century when anti-immigrant rhetoric led to draconian crackdowns on the movement of bodies, and it is true today as new measures seek to construct migrants as dangerous and undesirable. This premise forms the crux of Jay Timothy Dolmage's new book Disabled Upon Arrival: Eugenics, Immigration, and the Construction of Race and Disability, a compelling examination of the spaces, technologies, and discourses of immigration restriction during the peak period of North American immigration in the early twentieth century. Through careful archival research and consideration of the larger ideologies of racialization and xenophobia, Disabled Upon Arrival links anti-immigration rhetoric to eugenics--the flawed 'science' of controlling human population based on racists and ableist ideas about bodily values. Dolmage casts an enlightening perspective on immigration restriction, showing how eugenic ideas about the value of bodies have never really gone away and revealing how such ideas and attitudes continue to cast groups and individuals as disabled upon arrival." -- Publisher's description